Using non–Invasive genetic techniques to assist in maned wolf conservation in a remnant fragment of the Brazilian Cerrado - Mannise, Natalia; Trovati, R. Guilherme; Duarte, J. Mauricio B. [UNESP]; Maldonado, Jesús E.; González, Susana (Consorci del Museu de Ciencies Naturals de Barcelona, 2018)
Using non–invasive genetic techniques to assist in maned wolf conservation in a remnant fragment of the Brazilian Cerrado. The maned wolf is a South American canid considered a keystone species of the Cerrado. We performed a genetic assessment of maned wolves that inhabit a small remnant fragment of the Cerrado in Brazil. We collected 84 fecal samples over a year and also included two tissue samples from road–killed animals. We successfully identified the species, sex, and individuals using molecular markers. Using microsatellite loci analysis we identified 13 different individuals, eight females and five males. The genetic variability level found and the high number of individuals detected indicates the presence of an open population.
Utilización de técnicas genéticas no invasivas para contribuir a la conservación del aguará guazú en un fragment residual del Cerrado de Brasil
Keywords: Fecal DNA; Microsatellite loci; Neotropical canid; Real time PCR; ZFX–ZFY